1979
DOI: 10.1139/v79-172
|View full text |Cite
|
Sign up to set email alerts
|

Electronic excited states of small ring compounds. VII. Bicyclo[2.1.0]pentanes by the photocycloaddition of 1,2,3-triphenylcyclopropene to fumaro- and maleonitrile

Abstract: . Can. J. Chem. 57, 1037 (1979). Irradiation of the charge-transfer complex between 1,2,3-triphenylcyclopropene (1) and fumaronitrile (7) and maleonitrile (8) leads to formation of bicyclo[2.1 .O]pentane cycloaddition products (9, 10, 11) and the photoene product (12). These products were also formed when the reaction was photosensitized (triplet-triplet transfer). The structure of the adducts was established by analysis of 13C and 'Hmr spectra. Nuclear Overhauser effect studies were also useful. The triplet e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The triplet pairs possess an important additional decay channel, namely geminate combination to give triplet biradicals. Indirect formation of these key intermediates, via back electron transfer of triplet pairs to give one of the reactants in the triplet state followed by attack to ground state molecules, , is precluded by thermodynamics in the Paterno−Büchi systems studied . For the cycloadditions investigated in the present work, these indirect pathways would be thermodynamically feasible, and olefin triplets are indeed formed in the anethole/fumarodinitrile systems.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The triplet pairs possess an important additional decay channel, namely geminate combination to give triplet biradicals. Indirect formation of these key intermediates, via back electron transfer of triplet pairs to give one of the reactants in the triplet state followed by attack to ground state molecules, , is precluded by thermodynamics in the Paterno−Büchi systems studied . For the cycloadditions investigated in the present work, these indirect pathways would be thermodynamically feasible, and olefin triplets are indeed formed in the anethole/fumarodinitrile systems.…”
Section: Discussionmentioning
confidence: 77%
“…While the reactions of the former category have been extensively investigated, , much less is known about the mechanisms of reactions falling into the latter category . From sensitization and scavenging studies as well as from energetic considerations it was concluded that in polar solvents the [2 + 2] cycloadditions of 1,2,3-triphenylcyclopropene with electron-deficient olefins such as fumarodinitrile and the conceptually related [4 + 2] cycloaddition of a similar cyclopropene with dicyanoanthracene proceed by an electron-transfer/triplet mechanism: A radical ion pair is formed initially; this undergoes back electron transfer to give an olefin triplet (the cyclopropene triplet in these systems); attack by this species on the other olefin yields a triplet biradical which finally leads to the cycloadducts. As the primary excited species has singlet multiplicity in these reactions, intersystem crossing occurring in the radical ion pairs is therefore one of the key steps of this mechanism.…”
mentioning
confidence: 99%
“…Ibid. 1964, 86, 927 (7) Space group Pi; a = 11.878 ( 5), b = 20.915 ( 8), c = 13.056 (4) A; a = 90.93 (3), ß = 97.36 (3), y = 90.64 (3)°; Z = 2 (23 °C). A total of 7736 reflections were measured (CAD 4) for < 45°, of which 3109 were considered to be observed.…”
mentioning
confidence: 99%
“…The assumptions are further supported by a number of bimolecular photochemical reactions initiated by energy or charge (electron) transfer interactions wherein the excitation of the CT band of ground-state complexes generally leads to successful photoreactions. [24][25][26][27][28][29] In spite of these reports on energy and charge (electron) transfer interactions, the present observation is puzzling in that the excitation of Xs absorption at >400 nm causes no self-nitrosation of 1-NpOH. Since an exciplex is a loosely bound complex possessing an enthalpy of dissociation of <10 kcal/mol,30™32 cases of the reorientation of an exciplex faster than its reaction processes are known.20™29 However, in H abstraction from alkylbenzenes by the , * triplet states of aromatic ketones (by CT mechanism), two distinct and irreversible exciplexes have been identified to explain observed H-abstraction selectivity.…”
Section: Discussionmentioning
confidence: 93%